Oxidační stres v patofyziologii mužské neplodnosti - Oborná, Ivana (Iga MZ ČR, 2010)
Implementation of measurement of oxidative stress into the routine diagnostics of male factor infertility. Determination of chosen species of ROS/RNS in spermatozoa; discrimination of cell origin of chosen ROS by flow-cytometry. Evaluation of the effectof antioxidant therapy using lycopene on the total antioxidant capacity of blood and seminal plasma. The evaluation of the psychical discomfort and influence of psychological couselling.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: průtoková cytometrie; Semen Analysis; Infertility, Male; Free Radicals; andrologie; Oxidative Stress; Spermatozoa; oxidační stres; mužská infertilita; analýza spermatu; Antioxidants; volné radikály; farmacie a farmakologie; antioxidancia; biochemie; Flow Cytometry; spermie